FAKTOR-FAKTOR YANG MEMPENGARUHI KEPERCAYAAN, KEPUASAN DAN RELATIONSHIP COMMITMENT PELANGGAN PADA INDUSTRI JASA - Saparso (Media Riset Akuntansi, Auditing & Informasi, 2014)
The service industry has a substantial contribution compared to agriculture and industry with state revenues. Nevertheless, Indonesia is still the smallest compared to other large populated countries. It also proves that Indonesia has not maximized in exploiting the ability of purchasing power and economic growth achieved. The focus of this paper is to investigate the commitment commitment as central to the development of mercantile marketing. The factors that influence commitment to generate strong relationships are by maintaining a relationship to the level of customer commitment with the company. In particular, examine the factors that influence trust and satisfaction of the customer commitment. Therefore the proposed proposition is the factors that influence (economic content, resource content, social content, emotional content) trust (belief), satisfaction (satisfaction) and customer commitment relationship in the service industry.